ANALISIS PENERAPAN NILAI TRADISI ASWAJA DALAM BUDAYA DISKUSI ILMIAH MAHASISWA UNIVERSITAS ISLAM TRIBAKTI LIRBOYO - Moch Faqih; Ahmad Khoirul Mustamir; Muhammad Farid Asyasyauqi (PT. Saha Kreasi Indonesia, 2025)
This study aims to analyze the implementation of Aswaja (Ahlussunnah wal Jama’ah) traditions and values within the scientific discussion culture of students at Universitas Islam Tribakti Lirboyo. Employing a qualitative-descriptive approach and a case study design, data were collected through moderate participant observation, in-depth interviews, and documentation. The findings reveal that Aswaja traditions function not only as theological identity but also as an epistemological and methodological framework in students’ academic discourse. The classical dialectical method comprising qirā’ah, taḥlīl, taqrīr, naqḍ, tarjīḥ, and tasnīd is internalized as the primary analytical model in problem-solving. Aswaja values such as tawassuth (moderation), tawazun (balance), tasamuh (tolerance), and i‘tidal (justice) are clearly reflected in students’ scholarly ethics, argumentation patterns, and their responses to differing opinions. A pesantren educational background significantly enhances students’ ability to argue systematically, critically, and based on authoritative references. The study concludes that Aswaja traditions play a crucial role in shaping students’ intellectual character, maintaining academic moderation, and strengthening the quality of scholarly discussions, although the research remains limited by its specific institutional focus and the dominance of pesantren-based respondents.